Implementation of the Talking Stick Method in Islamic Education Learning as an Effort to Improve Student Learning Outcomes in Elementary Schools - Jailani (Barkah Publishing, 2024)
This study aims to improve student learning outcomes by applying the talking stick method. This study is a classroom action research. The subjects of this study were elementary school students. Data collection techniques used were observation and tests. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the talking stick method can improve elementary school students' learning outcomes. This can be seen from the increase in the average student learning which experienced an average increase with details of the first cycle 70.35, the second cycle 79.61 and the third cycle 87.03. Furthermore, the percentage of student completion also increased in each cycle with details of the first cycle 69.33%, the second cycle 76.57% and the third cycle 92.67%. Therefore, the talking stick method can be used as an alternative learning method for elementary school students.